Faktor Yang Memengaruhi Perilaku Perawat Terhadap Penerapan Sistem Manajemen Kesehatan Dan Keselamatan Kerja Di RSUD Langsa - Rosmawar -; Asriwati -; Achmad Rifai (Jurnal Kesmas Prima Indonesia, 2021)
The amount of risk from various potential hazards in the hospital so that efforts are needed to control and minimize the occurrence of work accidents, one of which is by implementing SMK3. This study aims to analyze the factors that influence nurses on the implementation of the occupational health and safety management system at Langsa City Hospital. The research design used an analytic survey with a cross sectional design. The sample of this study was 82 people used was simple random sampling. Data collection methods are primary data, secondary data and tertiary data. The research data were analyzed by univariate, bivariate and multivariate using logistic regression tests. The results showed that there was an effect of knowledge on the application of SMK3 (p = 0.002), there was an effect of attitude on the application of SMK3 (p = 0.010), there was an effect of action on the application of SMK3 (p = 0.005), there was an effect of perception on the application of SMK3 (p = 0.028) ), there is an effect of infrastructure on the implementation of SMK3 (p = 0.000), there is an effect of leadership support on the implementation of SMK3 (p = 0.021) and the most dominant variable is the action variable. Based on the research results, it can be concluded that there is an influence of knowledge, attitudes, actions, perceptions, infrastructure and leadership support on the implementation of SMK3 at Langsa Hospital. The suggestion in this research is that the hospital can adopt rifaskes innovation that can help the best health services for nurses.